2008
DOI: 10.1370/afm.890
|View full text |Cite
|
Sign up to set email alerts
|

The Hearing-Dependent Daily Activities Scale to Evaluate Impact of Hearing Loss in Older People

Abstract: PURPOSE We wanted to design and validate the Hearing-Dependent Daily Activities (HDDA) Scale as a means of identifying the impact of hearing loss in older persons by measuring capacity to carry out hearing-dependent activities. METHODSWe undertook a cross-sectional, observational study to validate a scale administered during a personal interview with 1,160 participants aged 65 years and older. When using the instrument to identify patients with hearing impairment, sensitivity and specifi city were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…5 By helping to identify the impact of hearing loss on the daily life of elderly patients, this instrument may be useful in tailoring access to audiology services.…”
Section: Access To Carementioning
confidence: 99%
“…5 By helping to identify the impact of hearing loss on the daily life of elderly patients, this instrument may be useful in tailoring access to audiology services.…”
Section: Access To Carementioning
confidence: 99%
“…Populational studies with elderly require further consistent data about communication disorders and their impact on the health of this population [3][4][5] . Considering that hearing loss the third most chronic illness reported by people aged 60 or more, the specifics of this problem require more research and analysis 6,7 . Epidemiological studies have shown risk factors for hearing loss in the elderly, Aging effects on the cochlea, the environment, genetic predisposition, health status and comorbidities, which could explain the wide variations at the beginning and degree of hearing loss in this age group 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, only 1.7% of elderly made use of hearing aid. Researches has demonstrated the existence of a positive correlation between the reduction of participation restriction in activities of daily living and the benefit obtained from the communication by elderly hearing aid users 6 . Thakur, Banerjee and Nikumb 40 identified 63.1% (257/407) of self-reported hearing loss in older adults, and only 1.47% (6/257) making use of hearing aid.…”
mentioning
confidence: 99%
“…There are various questionnaires available to measure the self-rated or subjective hearing impairment in different contexts. Some of them are for example the Hearing Handicap Inventory for the Elderly (HHIE) [21] to assess the effects of hearing impairment on the emotional and social adjustment of elderly people (25 items, two subscales) and its screening version (short form) HHIE-S (10 items), the Hearing-Dependent Daily Activities Scale (HDDA) [22] to measure the impact of hearing loss on daily life in the elderly (12 items, two factors), the Hearing Performance Inventory (HPI) [23] to assess self-reported hearing performance in problem areas experienced in everyday listening (90 items, six sections) and their short form HPI-S (31 items) [24], the McCarthy-Alpiner Scale of Hearing Handicap (M-A Scale) [25] that combines self-assessments and the attitude of family members of the hearing impaired person (34 items, three sections), or the Speech, Spatial and Qualities of Hearing Scale (SSQ) [26] that measures a broad range of hearing disabilities across different domains (50 items, three sections). All of them have in common that participants need their time to use them and they include the context.…”
Section: Introductionmentioning
confidence: 99%